Legal Liability for the Violation of Traffic Rules by a Person Subjected to an Administrative Penalty - A. S. Rubtsova (Сибирское юридическое обозрение)
In the article actual problems of qualification of repeated driving of a car, a tram or other mechanical vehicle by a person in the state of intoxication are considered (Article 264.1 of the Criminal Code of the Russian Federation). Ways to solve these problems are suggested. The problems of establishing administrative prejudice in criminal legislation are identified, taking into account the provisions of the decision of the Constitutional Court of the Russian Federation of February 10, 2017 no. 2-P. The problems of qualification of repeated driving of a vehicle by a person in the state of intoxication are investigated. It is substantiated that Art. 264.1 of the Criminal Code of the Russian Federation is a norm with double prevention. The conclusion is made that it is necessary to adopt a resolution of the Plenum of the Supreme Court of the Russian Federation where an interpretation will be given of the application of norms with administrative prejudice to develop a unified approach to understanding the criminalization of such acts and the grounds for prosecuting those who committed them.